The stone moved - Khan, Saniyasnain; Gurmeet (Goodword Kidz New Delhi, 2013)
The Prophet Muhammad came to us as Allah's last messenger to preach His Divine Message. The stories handed down to us of the Prophet Muhammad and his teachings show us the right path in all our everyday activities. Indeed, his life is an example in right living to us all. The Prophet Muhammad for Little Hearts series is especially designed to enable your children to learn and understand more about the Prophet's life in a natural and enjoyable way. It is a wonderful way to explain to children the meaning and purpose of the Prophet's life and message, and will encourage them to follow his teachings in their daily life. A simple text and magnificent color illustrations will captivate young, active minds. A Visit to Madinah is a beautifully illustrated and creatively written story about the Prophet Muhammad. It will capture the interest of children both at home and in the classroom.The Stone Moved is a well-narrated story originally told by the Prophet. It recounts the tale of three men stuck in a cave who depend on Allah$1 (Bs mercy to free them. Their tale is one that is sure to delight children young and old.This Story is a beautifully illustrated and creatively written book that narrates a tale told by Prophet Muhammad. The book teaches us that faith and good deeds alone will bring us salvation.s